The Signature of All Things : A novel (NY; Penguin Books, 2013)
In The Signature of All Things, Elizabeth Gilbert returns to fiction, inserting her inimitable voice into an enthralling story of love, adventure and discovery. Exquisitely researched and told at a galloping pace, The Signature of All Things soars across the globe$1 (Bfrom London to Peru to Philadelphia to Tahiti to Amsterdam, and beyond.s
English
Keywords: PN3311-3503 Literature (General)- Prose. Prose Fiction